Graft‐versus‐host disease after liver transplantation is associated with bone marrow failure, hemophagocytosis, and DNMT3A mutations. Issue 12 (19th July 2021) - Newell, Laura F.; Dunlap, Jennifer; Gatter, Ken; Bagby, Grover C.; Press, Richard D.; Cook, Rachel J.; Fletcher, Luke; Leonard, Jessica T.; Leong, Kelli M.; Bubalo, Joseph S.; Olyaei, Ali; Deloughery, Thomas G.; et al.
Abstract : Graft‐versus‐host disease after liver transplantation (LT‐GVHD) is rare, frequently fatal, and associated with bone marrow failure (BMF), cytopenias, and hyperferritinemia. Given hyperferritinemia and cytopenias are present in hemophagocytic lymphohistiocytosis (HLH), and somatic mutations in hematopoietic cells are associated with hyperinflammatory responses (clonal hematopoiesis of indeterminate potential, CHIP), we identified the frequency of hemophagocytosis and CHIP mutations in LT‐GVHD. We reviewed bone marrow aspirates and biopsies, quantified blood/marrow chimerism, and performed next‐generation sequencing (NGS) with a targeted panel of genes relevant to myeloid malignancies, CHIP, and BMF. In all, 12 marrows were reviewed from 9 LT‐GVHD patients. In all, 10 aspirates were evaluable for hemophagocytosis; 7 had adequate DNA for NGS. NGS was also performed on marrow from an LT cohort ( n = 6) without GVHD. Nine of 10 aspirates in LT‐GVHD patients showed increased hemophagocytosis. Five (71%) of 7 with LT‐GVHD had DNMT3A mutations; only 1 of 6 in the non‐GVHD LT cohort demonstrated DNMT3A mutation ( p = .04). Only 1 LT‐GVHD patient survived. BMF with HLH features was associated with poor hematopoietic recovery, and DNMT3A mutations were over‐represented, in LT‐GVHD patients. Identification of HLH features may guide prognosis and therapeutics. Further studies are needed to clarify the origin and impact of CHIP mutations on the hyperinflammatory state. Abstract : Histologic and genomic examination of bone marrow samples from patients with graft‐versus‐host disease occurring after liver transplantation reveals active hemophagocytosis and a striking over‐representation of DNMT3A mutations. Szabolcs comments on page 3823 .